Encyclopedia Brown and the case of the treasure hunt - Sobol, Donald J., 1924-; Owens, Gail (Toronto ; New York : Bantam, 1989)
America's Sherlock Holmes in sneakers continues his war on crime in ten more cases, the solutions to which are found in the back of the book.
Children's Catalog (Wilson)
Booklist
3-6
Keywords: Mystery and detective stories; Mystery and detective stories